Analysis of Organizational Culture and Work Discipline on The Performance of ASN Nurses in General Hospital in Kediri Regency - Sheilla Happy Putry; Panca Radono; Agustin Widyowati; sholichudin (Journal of Hospital Management and Services, 2026)
Hospitals, as healthcare institutions, require optimal performance from their healthcare workers. The performance of civil servant nurses at Kediri District Hospital (RSUD) shows disciplinary issues, such as late attendance and insufficient working hours, which can disrupt service quality. Organizational culture and work discipline are suspected to be important factors influencing nurse performance. This study used a quantitative approach with a cross-sectional design. The sample consisted of 86 civil servant nurses selected through simple random sampling. Data were collected using a questionnaire that had been tested for validity and reliability. Data analysis was performed using multiple linear regression to determine the effect of organizational culture and work discipline on nurse performance. The analysis results show that the organizational culture variable has a significant negative effect on performance, while the discipline variable has no significant effect. The organizational culture variable has a significance value of 0.019 with a regression coefficient value of -330. Because the significance value is negative than 0.05, this effect is considered significant but negative. Meanwhile, the discipline variable also shows an insignificant effect with a significance value of 0.694 and a regression coefficient of -0.051. These findings demonstrate the importance of implementing a positive organizational culture and enforcing work discipline as an effort to improve service quality. Hospital management is advised to strengthen a work culture that supports and enforces discipline as part of an effective human resource management system.